3D characterisation of the Fe-rich intermetallic phases in recycled Al alloys by synchrotron X-ray microtomography and skeletonisation. (15th March 2018) - Zhao, Y.; Du, W.; Koe, B.; Connolley, T.; Irvine, S.; Allan, P.K.; Schlepütz, C.M.; Zhang, W.; Wang, F.; Eskin, D.G.; Mi, J.
Abstract: Synchrotron X-ray microtomography and skeletonisation method were used to study the true 3D network structures and morphologies of the Fe-rich intermetallic phases in recycled Al-5.0%Cu-0.6%Mn alloys with 0.5% and 1.0% Fe. It was found that, the Fe-phases in the 1.0%Fe alloy have node lengths of 5–25 μm; while those in the 0.5%Fe alloy are of 3–17 μm. The Fe-phases in the 1.0%Fe alloy also developed sharper mean curvature with wider distribution than those in the 0.5%Fe alloy. Combining SEM studies of the deeply-etched samples, the true 3D structures of 4 different type Fe phases in both alloys are also revealed and demonstrated. Graphical abstract: Image 1